Gamification as New Trend in Creating Market Place Customer Engagement on Young Housewife: SMART Model Analysis - Rita Kusumadewi; Budi Rusdian; Farihatu Aini; Riza Mahmud Yunus (UPT Publikasi Ilmiah UNISBA, 2026)
Customer engagement has become a key strategy for sustaining long-term relationships between marketplaces and customers. Although gamification has been widely implemented by e-commerce platforms, limited studies have examined how SMART model-based gamification influences customer engagement, particularly among young housewives, who represent a significant segment of online marketplace users in Indonesia. This study addresses this research gap by examining the effect of SMART model gamification on customer engagement and contributes to the literature by extending the application of the SMART model within the context of marketplace gamification. A quantitative research design was employed using a purposive sampling method. Data were collected through an online questionnaire distributed to 100 young housewives aged 20–40 years who had played games on marketplace platforms at least once. The data were analyzed using simple linear regression analysis to examine the relationship between SMART model gamification and customer engagement. The findings indicate that SMART model gamification has a positive and statistically significant effect on customer engagement in online marketplaces. These results suggest that well-designed gamification features can strengthen customer interaction, participation, and loyalty. The study provides practical implications for marketplace managers by highlighting the importance of incorporating meaningful and engaging game elements to enhance customer engagement and maintain long-term customer relationships.